2017
DOI: 10.1155/2017/1762042
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Erosion of Cement-Bentonite via Piping

Abstract: Cement-bentonite is one of the main materials used in the seepage barriers to protect earth dams and levees from water erosion. However, the current understanding of the erodibility of the cementitious materials and the interactions between cracked seepage barriers and the water flow is inadequate. Based on the laboratory pinhole erosion test, we first investigated the impacts of cementbentonite treatments by using the ground granulated blast-furnace slag (GGBS) as replacement on the erosion characteristics, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…It can be seen that the effects of the eroding time on the CEML of CIL with different cement contents (2%, 3%, 4%, and 6%) are consistent, which indicates that there is a good linear correlation between the eroding time and the CEML of CIL. Moreover, these findings are in agreement with research that showed that there is an overall increase in the erosion of cement-bentonite when there is an increase in the erosion time [2].…”
Section: Influence Of the Compactionsupporting
confidence: 92%
See 1 more Smart Citation
“…It can be seen that the effects of the eroding time on the CEML of CIL with different cement contents (2%, 3%, 4%, and 6%) are consistent, which indicates that there is a good linear correlation between the eroding time and the CEML of CIL. Moreover, these findings are in agreement with research that showed that there is an overall increase in the erosion of cement-bentonite when there is an increase in the erosion time [2].…”
Section: Influence Of the Compactionsupporting
confidence: 92%
“…To find methods of improving the erosion resistance of the subgrade, studies have researched how the strength of the subgrade filler could be improved and how eroding tests could be optimized according to the actual situation of the subgrade and have proposed antierosion measures. In particular, extensive attention has been paid to efforts that seek to improve the strength of subgrade materials, and some chemical binders, such as cement [1][2][3][4], lime [5], nano-MgO [6], coal ash [7], fiber [8], marine-dredged soil [9], sustainable regenerated binding materials [10], and manganese slag [11], have been applied to the subgrade to investigate their effect on the water stability and the erosion resistance of the soil subgrade. Researchers at home and abroad have found that using the aforementioned materials (especially cement) not only greatly increases the strength of the subgrade, but also additionally improves the water damage resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on levees, which have been performed in South Korea and other countries, include small-scale experiments for understanding the formation and process of an overtopping breach or erosion according to the levee material (e.g., [1][2][3][4]); a levee model experiment under most real-scale conditions, which could minimize the scale effect for analyzing the breach behavior according to the seepage and overflow (e.g., [5][6][7][8][9]); an analysis of the retardation effects on a levee breach from the use of reinforcement methods (e.g., [10,11]); an investigation of improving the stability of the levee against erosion and infiltration using mixed materials with cement (e.g., [12][13][14][15]); and methods of improving soil behavior using biopolymers (e.g., [16,17]). All advanced countries should establish and implement effective countermeasures to prevent levee erosion from flooding.…”
Section: Introductionmentioning
confidence: 99%